An Open-label Trial of Adjuvant High-frequency Left Prefrontal Repetitive Transcranial Magnetic Stimulation for Treating Suicidal Ideation in Adolescents and Adults With Depression. Issue 2 (June 2021) - Zhang, TianHong; Zhu, JunJuan; Wang, JunJie; Tang, YingYing; Xu, LiHua; Tang, XiaoChen; Hu, YeGang; Wei, YanYan; Cui, HuiRu; Liu, XiaoHua; Hui, Li; Li, ChunBo; et al.
Abstract : Background: Repetitive transcranial magnetic stimulation (rTMS) offers promise for the treatment of depression, yet its potential impact on suicidal ideation (SI), particularly in adolescents, has not been well studied. This study aimed to investigate the efficacy of add-on rTMS for reducing SI in a large clinical sample experiencing an acute phase of depression. Methods: This study included 146 patients with a score of ≥14 on the 17-item Hamilton Rating Scale for Depression (HAMD). Among them, 97 had a HAMD-SI (3-item) score of 1 or greater and were pooled into the analysis. Symptoms of depression and SI were measured using the HAMD total score and HAMD-SI score. Comparisons of clinical improvement for both SI and rates of remission were made between adolescent (n = 29) and adult patients (n = 68), as well as between high-frequency (HF) rTMS on the left dorsolateral prefrontal cortex (DLPFC) (80 trains, 30 pulses per train, 12 s intertrain interval, 2400 pulses per session) and low-frequency (LF) rTMS on the right DLPFC protocol (2 trains, 700 pulses per train, 1 s intertrain-interval, 1400 pulses per session), power (intensity) level of 120% of motor threshold (MT), and 5 sessions per week for 2 weeks. Results: Add-on rTMS treatment showed significant clinical improvement in SI, and was also well tolerated, with no adverse events reported. The SI improvements and remission rates were more significant in adolescents treated with the HF left DLPFC rTMS protocol, compared with adults treated with the LF right DLPFC rTMS protocol (remission rates: adolescent with LF right DLPFC, 50%; adolescent with HF left DLPFC, 94%; adult with LF right DLPFC, 65%; adult with HF left DLPFC, 57%). A positive association between improvement in the HAMD total score and HAMD-SI score was found in adults, but not in adolescents. Conclusions: Add-on rTMS treatment for SI associated with depression is promising with respect to safety and feasibility. Our preliminary evidence supports an extension of the application of rTMS to adolescent patients with SI during the acute phase of depression, in addition to its use in adult treatment-resistant depression. Abstract : Supplemental digital content is available in the text.